Traumatic brain injury-induced dysregulation of the circadian clock. - Deborah R Boone (Public Library of Science (PLoS), 2012)
Circadian rhythm disturbances are frequently reported in patients recovering from traumatic brain injury (TBI). Since circadian clock output is mediated by some of the same molecular signaling cascades that regulate memory formation (cAMP/MAPK/CREB), cognitive problems reported by TBI survivors may be related to injury-induced dysregulation of the circadian clock. In laboratory animals, aberrant circadian rhythms in the hippocampus have been linked to cognitive and memory dysfunction. Here, we addressed the hypothesis that circadian rhythm disruption after TBI is mediated by changes in expression of clock genes in the suprachiasmatic nuclei (SCN) and hippocampus. After fluid-percussion TBI or sham surgery, male Sprague-Dawley rats were euthanized at 4 h intervals, over a 48 h period for tissue collection. Expression of circadian clock genes was measured using quantitative real-time PCR in the SCN and hippocampus obtained by laser capture and manual microdissection respectively. Immunofluorescence and Western blot analysis were used to correlate TBI-induced changes in circadian gene expression with changes in protein expression. In separate groups of rats, locomotor activity was monitored for 48 h. TBI altered circadian gene expression patterns in both the SCN and the hippocampus. Dysregulated expression of key circadian clock genes, such as Bmal1 and Cry1, was detected, suggesting perturbation of transcriptional-translational feedback loops that are central to circadian timing. In fact, disruption of circadian locomotor activity rhythms in injured animals occurred concurrently. These results provide an explanation for how TBI causes disruption of circadian rhythms as well as a rationale for the consideration of drugs with chronobiotic properties as part of a treatment strategy for TBI.